2002
DOI: 10.1113/jphysiol.2001.018333
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels Kv1.1, Kv1.2 and Kv1.6 influence excitability of rat visceral sensory neurons

Abstract: Voltage-gated potassium channels, Kv1.1, Kv1.2 and Kv1.6, were identified as PCR products from mRNA prepared from nodose ganglia. Immunocytochemical studies demonstrated expression of the proteins in all neurons from ganglia of neonatal animals (postnatal days 0-3) and in 85-90 % of the neurons from older animals (postnatal days 21-60). In voltage clamp studies, a-dendrotoxin (a-DTX), a toxin with high specificity for these members of the Kv1 family, was used to examine their contribution to K + currents of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
108
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 35 publications
17
108
0
Order By: Relevance
“…Previous studies in rats showed that there was only a small effect on the duration or amplitude of the action potential when ␣-DTXsensitive channels were blocked (Glazebrook et al, 2002). This reflected the short duration of the action potential relative to the activation time of Kv1.1.…”
Section: Role Of Kv11 In Petrosal Gangliamentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in rats showed that there was only a small effect on the duration or amplitude of the action potential when ␣-DTXsensitive channels were blocked (Glazebrook et al, 2002). This reflected the short duration of the action potential relative to the activation time of Kv1.1.…”
Section: Role Of Kv11 In Petrosal Gangliamentioning
confidence: 99%
“…Kv1.1 activates sufficiently rapidly that its block reduces the depolarizing current necessary to elicit an action potential near threshold. Block of Kv1.1 also reduces the afterhyperpolarization, thus contributing to repetitive discharge (Glazebrook et al, 2002). These effects on visceral sensory neurons predicted that alterations in the autonomic nervous system may occur in Kv1.1-null mice and, possibly, in EA-1 individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many sensory neurons are sensitive to the dendrotoxins that inhibit K V 1 delayed rectifying K + channels (Harvey 2001), resulting in increased excitability. In some cases, dendrotoxin converts phasic neurons to tonic (Glazebrook et al 2002;Catacuzzeno et al 2008), indicating that K V 1.1 and K V 1.2 channels are essential to keep phasic neurons phasic. Reduction in the level of dendrotoxin-sensitive K + current is associated with the increase in excitability after nerve damage (Song et al 2012).…”
Section: Membrane Properties Associated With Tonic and Phasic Firing mentioning
confidence: 99%